A Study on Service Quality of Banks in Tricity - Ruby Sharma, Pallavi Pahuja (International Journal of Advanced Science and Technology, 2020)
Banks, their products, working all are important as they are important pillars of any economy. Service sector is quite competitive as it involves qualitative factors than quantitative. Banking a leading service sector is no way an exception. Due to change in business environment, opening of global market, unparalleled competition banks have to provide updated service to its customers to beat these market forces. Almost all banks offer same type of products but the way of delivering these products to customers is the thing that makes a difference for banks and ultimately effects their customer base and profitability. Due to competition banks have to be very particular for their service quality. One of the reliable ways to measure service quality is SERVQUAL. In the present study RATER modal is used to measure service quality of banks operating in tricity.